DEVELOPMENT OF SMALL BUSINESS IN RURAL SETTLEMENTS - Abdulkadirov1, Umalt; Lukovtseva, Anna; Osmanov, Ruslan (Revista Inclusiones, 2020)
Under current conditions, an important role in the formation of an effective, socially-oriented economy is assigned to entrepreneurship. The development of entrepreneurship contributes to creating the necessary conditions for the integrated development of rural areas, solving social problems in villages, and ensuring food security of the country. The article deals with the issue of state support for small business development in rural settlements and presents the outcomes of the conducted theoretical analysis of the small business development laws in rural areas. Based on the results of the expert survey, the mechanisms, tools, and means of implementing the state policy for the development of small business in rural settlements are identified, as well as the characteristics of the state policy for the development of small business in rural settlements are presented along with the consideration of the European experience in concerned field.